2010
DOI: 10.1007/s13197-010-0133-y
|View full text |Cite
|
Sign up to set email alerts
|

Studies on physico-chemical changes during artificial ripening of banana (Musa sp) variety ‘Robusta’

Abstract: Banana (Musa sp var 'Robusta') fruits harvested at 75-80% maturity were dip treated with different concentrations of ethrel (250-1,000 ppm) solution for 5 min. Ethrel at 500 ppm induced uniform ripening without impairing taste and flavour of banana. Untreated control banana fruits remained shriveled, green and failed to ripen evenly even after 8 days of storage. Fruits treated with 500 ppm of ethrel ripened well in 6 days at 20±1°C. Changes in total soluble solids, acidity, total sugars and total carotenoids s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 13 publications
14
35
0
Order By: Relevance
“…The increase in taste during ripening was due to the increase in certain volatile compounds which acted as a precursor for taste in the fruit cells. The findings of Kulkarni et al (2011) in banana cv. Robusta, Mahajan et al (2010) in cv.…”
Section: Results and Discussion:-mentioning
confidence: 93%
“…The increase in taste during ripening was due to the increase in certain volatile compounds which acted as a precursor for taste in the fruit cells. The findings of Kulkarni et al (2011) in banana cv. Robusta, Mahajan et al (2010) in cv.…”
Section: Results and Discussion:-mentioning
confidence: 93%
“…All the fruits were ripened at 8 th days of storage except control.The mode of action of ethylene on ripening of fruits is not clearly understood. However it was explained by Holl (1977) Kulkarni et al (2011) also noted that ethrel @ 500 ppm induced uniform ripening without impairing taste and flavour of banana. Similarly, Mahajan et al (2010) observed that treatment of bananas with ethylene gas (100 ppm) or ethephon (500 ppm) resulted in adequate ripening of fruits after 4 days with uniform colour, pleasant flavour, desirable firmness and acceptable quality and better shelf-life.…”
Section: Resultsmentioning
confidence: 99%
“…of variety 'Robusta' were procured at the maturity stage 1 (all green) from selected banana orchards near Anand city (India). The procured material was sorted, tagged and kept for ripening as per the method suggested by Kulkarni et al, (2010) up to 7 th stage of maturity. Commercial pectinolytic enzyme i.e.…”
Section: Methodsmentioning
confidence: 99%